Factors associated with the Household Income of Persons Living with HIV/AIDS in China - Zhang, Xiulan (Glob J Health Sci, 2012)
This study provides a profile of 866 people living with HIV/AIDS (PLWHA) in three provinces in rural China and identifies factors associated with per-capita income in AIDS-affected households. The majority of the participants were female, married, had completed primary school, and were 30-49 years of age. Thirty percent of respondents lived in a household with at least one other HIV/AIDS patient and 15% had experienced the death of a household member due to HIV/AIDS. Therefore, health professionals should be aware of issues of grief and caregiver burnout among rural PLWHA and their families. Three-quarters of the respondents continued to work after being diagnosed with HIV/AIDS. Household per capita income was significantly higher for married individuals and those still working. Possible government and workplace policy initiatives that endeavor to increase income and mitigate the economic impact of HIV/AIDS on households are discussed.